Screening of Monascus spp. on water-soluble adipogenesis inhibitory activity - Wanniaika, I.P.; Niroshie, P.A.B.; Kaumal, M.N.; Hettiarachchi, C. (University of Colombo, 2020)
Monascus-fermented rice, which is known as red mold rice has been used as Chinese herbal medicine for treating hyperlipidemia for many years. Monacolin K and citrinin, showing adipogenesis inhibitory activity, are water-insoluble secondary metabolites of Monascus spp. However, less attention has been paid regarding water-soluble adipogenesis inhibitors from Monascus spp. Thus, the current study was conducted to screen Monascus fungi for their watersoluble adipogenesis inhibitors. A total of 25 strains of Monascus fungi were used in screening for water-soluble adipogenesis inhibitors. Monascus strains were maintained on potato dextrose agar (PDA) medium at 30 °C for 7 and 10 days, and the spores of these strains were collected and stored separately at 4 °C until further use. Each strain was cultivated on steamed rice (RMR) and barley (RMB) separately at 30 °C and 35 °C for 7 and 14 days, and their respective water extracts were prepared. Cell viability was determined by MTT assay, and the accumulation of triglycerides in adipocytes was examined by oil red O staining using mouse 3T3-L1 cells. Results of MTT assay confirmed that all tested samples do not affect the viability of 3T3-L1 cells, and this confirmed that the reduction of lipid accumulation is not due to any cell death, but due to a secondary metabolite/s produced during the production of RMR or RMB. Moreover, TLC results revealed that water-soluble fractions of both RMR and RMB are free from lovastatin and citrinin. According to the obtained results, it can be concluded that the water extracts of RMR showed a higher adipogenesis inhibitory activity than that of RMB. Further, since it showed a significantly low lipid accumulation percentage (61.86% ± 3.6) M. pilosus NBRC4507 grown at 30 °C for 14 days was selected as the best strain and the cultivation condition respectively, in production of RMR with higher adipogenesis inhibitory activity.
Keywords: Adipogenesis inhibitors; Genus Monascus; lipid accumulation inhibition; red mold rice; water-soluble